DETERMINAN KEPUTUSAN PEMBELIAN KOSMETIK HALAL OLEH MUSLIMAH MILENIAL DI INDONESIA - Yuni Ratnawati; Saiful Anwar (LP2M Universitas Bina Bangsa, 2021)
The research aims to knowing the influence of the halal label, celebrity endorser, and word of mouth to decision with buying interest as an intervening variable by muslimah milenial cosmetics “PIXY” user. The population in this research is follower account Instagram @pixycosmetics who uses the product. The technique of sampling with a purposive random sampling method. As for the samples taken are as much as 102 respondents with a questionnaire to collect data. The program to analyze the data using SPSS 25.0. Analysis tool used is the path analysis. The result of this research show that: halal label, celebrity endorser, and word of mouth has a positive and insignificant influence to decision. Halal label and celebrity endorser also have a positive and insignificant influence to purchase interest, while word of mouth has a positive and significant effect on purchase interest. Meanwhile, purchase interest has a positive and significant effect on decisions. Purchase interest cannot be an intervening variable between halal labels on decision, but purchase interest can become an intervening variable between celebrity endorser and word of mouth on decisions